2017
DOI: 10.1186/s12940-017-0245-1
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations for heat-stress illness varies between rural and urban areas: an analysis of Illinois data, 1987–2014

Abstract: BackgroundThe disease burden due to heat-stress illness (HSI), which can result in significant morbidity and mortality, is expected to increase as the climate continues to warm. In the United States (U.S.) much of what is known about HSI epidemiology is from analyses of urban heat waves. There is limited research addressing whether HSI hospitalization risk varies between urban and rural areas, nor is much known about additional diagnoses of patients hospitalized for HSI.MethodsHospitalizations in Illinois for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
0
13
0
1
Order By: Relevance
“…Most of the studies only included direct impacts in the economic valuation: mortality [ 40 , 54 , 56 – 68 ], hospital admissions or outpatient visits (emergency room visits, hospitalizations, outpatient consultations, etc.) [ 38 , 40 , 54 , 56 58 , 62 – 64 , 67 , 69 72 ] or the loss of production associated with morbidity [ 40 , 56 , 58 , 63 , 66 , 71 ]. Fourteen studies built a model to obtain the number of hospital admissions or outpatient visits associated with heat waves [ 40 , 54 , 56 64 , 69 , 71 , 72 ], while the others did not specify their method of calculation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies only included direct impacts in the economic valuation: mortality [ 40 , 54 , 56 – 68 ], hospital admissions or outpatient visits (emergency room visits, hospitalizations, outpatient consultations, etc.) [ 38 , 40 , 54 , 56 58 , 62 – 64 , 67 , 69 72 ] or the loss of production associated with morbidity [ 40 , 56 , 58 , 63 , 66 , 71 ]. Fourteen studies built a model to obtain the number of hospital admissions or outpatient visits associated with heat waves [ 40 , 54 , 56 64 , 69 , 71 , 72 ], while the others did not specify their method of calculation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 38 , 40 , 54 , 56 58 , 62 – 64 , 67 , 69 72 ] or the loss of production associated with morbidity [ 40 , 56 , 58 , 63 , 66 , 71 ]. Fourteen studies built a model to obtain the number of hospital admissions or outpatient visits associated with heat waves [ 40 , 54 , 56 64 , 69 , 71 , 72 ], while the others did not specify their method of calculation. All the studies found the estimated health costs of heat waves to be significant.…”
Section: Discussionmentioning
confidence: 99%
“…Like rural areas, even smaller more spread-out cities lack heat adaptations and warning systems as the risk of heat exposure is underestimated when compared with more densely populated urban centers [78]. The least populated areas of Illinois had average annual hospitalization rate due to heat stress of 1.16 hospitalizations per 100,000 people, while metropolitan areas had 0.45 hospitalizations per 100,000 people [79].…”
Section: Ruralmentioning
confidence: 99%
“…Urban citizens should be better educated to counteract urban overheating, especially during heat waves. They should indeed effectively operate passive cooling strategies, given the well-known role of UHI and heat waves on population health diseases risk (Huber, Ibarreta, & Frieler, 2017;Jagai, Grossman, Navon, Sambanis, & Dorevitch, 2017;Schuster, Honold, Lauf, & Lakes, 2017;Youngsteadt, Ernst, Dunn, & Frank, 2017).…”
Section: Conclusion: Future Needs and Prioritiesmentioning
confidence: 99%